Molecular and phenotypic characteristics of methicillin-resistant Staphylococcus aureus isolated from hospitalized patients - Caio Ferreira de Oliveira; Alexandre Tadachi Morey; Jussevania Pereira Santos; Ludmila Vilela Pereira Gomes; Juscélio Donizete Cardoso; Phileno Pinge-Filho; Márcia Regina Eches Perugini; Lucy Megumi Yamauchi; Sueli Fumie Yamada-Ogattta (Journal of Infection in Developing Countries)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the leading causes of infections acquired in both community and hospital settings. In this study, MRSA isolated from different sources of hospitalized patients was characterized by molecular and phenotypic methods. Methodology: A total of 123 S. aureus isolates were characterized according to their genetic relatedness by repetitive element sequence based-PCR (REP-PCR), in vitro antimicrobial susceptibility profile, SCCmec typing and presence of seven virulence factor-encoding genes. Results: REP-PCR fingerprinting showed low relatedness between the isolates, and the predominance of one specific lineage or clonal group was not observed. All isolates were susceptible to teicoplanin and linezolide. All isolates were resistant to cefoxitin and penicillin, and the majority were also resistant to one or more other antimicrobials. Fifty isolates (41.7%) were intermediately resistant to vancomycin. Most isolates harbored SCCmec type II (53.7%), followed by type I (22.8%), type IV (8.1%) and type III (1.6%). All isolates harbored at least two virulence factor-encoding genes, and the prevalence was as follows: coa, 100%; icaA, 100%; hla, 13.0%; hlb, 91.1%, hld, 91.1%; lukS-PV and lukF-PV, 2.4%; and tst, 34.1%. A positive association with the presence of hla and SCCmec type II, and tst and SCCmec type I was observed. Conclusion: This study showed the high virulence potential of multidrug-resistant MRSA circulating in a teaching hospital. A high prevalence of MRSA showing intermediate vancomycin resistance was also observed, indicating the urgent need to improve strategies for controlling the use of antimicrobials for appropriate management of S. aureus infections.